Secondary School Students’ Disaster Preparedness Perception: A Mixed Method Approach - Kuloğlu, Ayşenur; Tutus, Fatma; Özer, Merve (My University, 2024)
The aim of this study was to examine the disaster preparedness perceptions and opinions of Secondary School Students who experienced the most recent major earthquake in Elazığ and Kahramanmaraş in Türkiye. The study population consisted of Secondary School Students in Elazığ and Kahramanmaraş during the 2022-2023 academic year. The sample included 548 participants in the quantitative part selected through non-probabilistic convenient sampling and 40 participants in the qualitative part selected using a criterion sampling method. In this study, a convergent parallel design, a mixed research method, was employed. The \"Disaster Preparedness Scale\" was used to collect quantitative data. The reliability of the scale was assessed using the Cronbach’s Alpha, which was found to be .82. Qualitative data were collected through a semi-structured interview form developed by the researchers. The results indicated that the disaster preparedness perceptions of the participants were at a moderate level. There was no significant difference in the disaster preparedness perceptions among participants based on gender, while significant differences were identified based on city (in favor of students in Elazığ), grade, maternal education level, and paternal education level. Qualitative findings suggested that participants perceived the misinformation in the media after disasters as a significant problem. They also mentioned preparing disaster kits as a precaution after disasters, receiving fire and earthquake-related training at their schools, but feeling that these trainings did not contribute significantly to their preparedness. Participants emphasized the need for disaster awareness education and call for realistic and effective training exercises.
Keywords: Disaster; Secondary School Students; Disaster Preparedness